استعانة النبي صلى الله عليه وسلم بالله تعالى في السيرة النبوية – دراسة تحليلية: The Prophet’s Reliance on Allah in the Prophetic Biography: An Analytical Study - عبد الكريم بن عيسى الرحيلي (الدراسات الإسلامية, 2025)
This study examines the concept of isti‘ānah (seeking divine assistance) as reflected in the Sirah of the Prophet Muhammad (PBUH). The research begins by defining isti‘ānah linguistically and in Islamic legal terminology, establishing its foundational significance in Islamic thought. It then proceeds through two main sections. The first section explores scriptural and historical evidence demonstrating the exalted status of reliance upon Allah in the Prophetic model, drawing upon the Qur’an, Sunnah, and statements of the early generations to highlight its centrality in the life of faith. The second section presents an analytical study of the manifestations of isti‘ānah in the Sirah, focusing specifically on its highest and most comprehensive form: supplication (du‘ā’). As the essence and core of worship, du‘ā’ embodies humility, submissiveness, and complete dependence upon Allah—traits repeatedly praised in the prophetic narratives and exemplified by the prophets. The study concludes by presenting the key findings, followed by practical recommendations that underscore the enduring relevance of isti‘ānah in contemporary spiritual and ethical life.